-12 (x - 5) + 15 (6-x)=42
tìm x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1/ `|x|=10<=> x=\pm 10`
2/ `|x-8|=0<=>x-8=0<=>x=8`
3/ `7+|x|=12<=>|x|=5<=>x=\pm 5`
4/ `|x+1|=3`
$\Leftrightarrow\left[\begin{array}{1}x+1=3\\x+1=-3\end{array}\right.\\\Leftrightarrow\left[\begin{array}{1}x=3\\x=-4\end{array}\right.$
5/ `15-x=16-(14-42)`
`<=>15-x=16+28`
`<=>15-x=44`
`<=>x=-29`
6/ `210-(x-12)=168`
`<=>210-x+12=168`
`<=>222-x=168`
`<=>x=54`
a, 2 x 31 x 12 + 4 x 6 x 42 + 8 x 27 x 3
= 2 x 12 x 31 + 4 x 6 x 42 + 8 x 3 x 27
= 24 x 31 + 24 x 42 + 24 x 27
= 24 x ( 31 + 24 + 27 )
= 24 x 82
= 1968
b, 2 x 53 x 12 + 4 x 6 x 87 - 3 x 8 x 40
= 24 x 53 + 24 x 87 - 24 x 40
= 24 x ( 53 + 87 - 40 )
= 24 x 100
= 2400
c, Tương tự
\(\frac{35}{x}=\frac{15}{12}\Leftrightarrow x=35.12:15=28\)
\(-\frac{2,6}{x}=-\frac{12}{42}\Leftrightarrow\frac{-2,6}{x}=-\frac{2}{7}\Leftrightarrow x=-2,6.7:\left(-2\right)=\frac{91}{10}\)
\(\frac{125}{10}=\frac{x}{45}\Leftrightarrow x=125.45:10=562,5\)
\(\frac{x^2}{6}=\frac{24}{25}\Leftrightarrow x^2=6.24:25=\frac{144}{25}\Leftrightarrow x=\sqrt{\frac{144}{25}}\Leftrightarrow x=\frac{12}{5}\)
1; \(\dfrac{35}{x}\) = \(\dfrac{15}{12}\) (\(x\ne\) 0)
⇒ \(x\) = 35 : \(\dfrac{15}{12}\)
⇒ \(x\) = 28
Vậy \(x=28\)
a) => y+42+2y= -12-14+2y
y+2y-2y = -12-14-42
y= -68
b) => 15+y-5-5y= -12-5y
y-5y+5y= -12-15+5
y = -22
c) => 2y+5-8y+21= -3-5y-2
2y-8y+5y= -3-2-5-21
-y= -31=>y=31
d)=> -13+3y+23= -120+y
3y-y= -120+13-23
2y= -130=>y= -65
e) => -21+32+5y= 16+4y
5y-4y= 16+21-32
y= 5
bài 1
a)y-(-42-2y) = (-12) - 14 +2y
y +42 + 2y = -12 -14 +2y
3y + 42 = -26 +2y
y = -68
b)15-(-y+5)-5y=-(12+5y+2)
15+y-5-5y=-12-5y-2
10-4y=-14-5y
-4y+5y=-14-10=-24
c)2y-(-5+8y-21)=-3-(5y+2)
2y+5-8y+21=-3y-5y-2
-6y+26=-8y-2
-6y+8y=-2-26
2y=-28
y=-28/2=-14
a,\(\frac{11}{12}-\left(\frac{5}{42}-x\right)=\frac{15}{28}-\frac{11}{12}\)
\(\Leftrightarrow\frac{11}{12}-\frac{5}{42}+x=\frac{15}{28}-\frac{11}{12}\)
\(\Leftrightarrow x=\frac{15}{28}-\frac{11}{12}-\frac{11}{12}+\frac{5}{42}\)
\(\Leftrightarrow x=\left(\frac{15}{28}+\frac{5}{42}\right)-\left(\frac{11}{12}+\frac{11}{12}\right)\)
\(\Leftrightarrow x=\frac{55}{84}-\frac{11}{6}\)
\(\Leftrightarrow x=\frac{-33}{28}\)
b, \(\frac{x+1}{10}+\frac{x+1}{11}+\frac{x+1}{12}=\frac{x+1}{13}+\frac{x+1}{14}\)
\(\Leftrightarrow\frac{x+1}{10}+\frac{x+1}{11}+\frac{x+1}{12}-\frac{x+1}{13}-\frac{x+1}{14}=0\)
\(\Leftrightarrow\left(x+1\right)\left(\frac{1}{10}+\frac{1}{11}+\frac{1}{12}-\frac{1}{13}-\frac{1}{14}\right)=0\)
\(\Leftrightarrow x+1=0\)
\(\Leftrightarrow x=-1\)
\(-12\left(x-5\right)+15\left(6-x\right)=42\)
=>\(-12x+60+90-15x=42\)
=>-27x=42-150=-108
=>\(x=\dfrac{-108}{-27}=4\)
\(-12\left(x-5\right)+15\left(6-x\right)=42\\ \Rightarrow-12x+12\cdot5+15\cdot6-15\cdot x=42\\ \Rightarrow-12x+60+90-15x=42\\ \Rightarrow-27x+150=42\\ \Rightarrow-27x=42-150\\ \Rightarrow-27x=-108\\\Rightarrow x=-108:\left(-27\right)\\ \Rightarrow x=4\)